Menopausal hormone therapy and cancer risk: An overestimated risk?. (October 2017) - Simin, Johanna; Tamimi, Rulla; Lagergren, Jesper; Adami, Hans-Olov; Brusselaers, Nele
Abstract: Aim: We aimed to assess the overall cancer risk among contemporary menopausal hormone therapy (MHT) users in Sweden and the risk for different cancer types. Methods: A nationwide Swedish population-based cohort study including all 290, 186 women aged ≥ 40 years having used systemic MHT during the study period (July 2005 and December 2012), compared with the Swedish female background population. MHT ever-use (all MHT, oestrogen-only MHT [E-MHT] and oestrogen plus progestin MHT [EP-MHT]) was based on the nationwide Prescribed Drug Registry. Cancer diagnoses were grouped into 16 different anatomical locations, for which standardised incidence ratios (SIRs) and 95% confidence intervals (CIs) were calculated. Results: The SIR of any cancer was 1.09 (95% CI: 1.07–1.11) following ever MHT, 1.04 (95% CI: 1.01–1.06) for E-MHT and 1.14 (95% CI: 1.12–1.17) for EP-MHT. The highest SIR was found for EP-MHT among users aged ≥70 years (SIR = 1.33, 95% CI: 1.26–1.40). The risk for invasive breast, endometrial or ovarian cancer combined was increased for any MHT (SIR = 1.31, 95% CI: 1.28–1.34). The risk of invasive breast cancer was increased following MHT and increased with age for EP-MHT users. The risk of gastrointestinal cancers combined was decreased (SIR = 0.90, 95% CI: 0.86–0.94), particularly the oesophagus (SIR = 0.81, 95% CI: 0.64–1.00), liver (SIR = 0.81, 95% CI: 0.65–0.99) and colon (SIR = 0.90, 95% CI: 0.84–0.95). Conclusions: MHT, notably EP-MHT, was associated with a limited increase in overall cancer risk. The increased risk of female reproductive organ cancers was almost balanced by a decreased risk of gastrointestinal cancers. Highlights: Menopausal hormone therapy (MHT) is the single most effective treatment for menopause-related symptoms. Its use declined after 2002 because of a reported elevated breast cancer risk. Little is known on the overall cancer risk or other cancer types. This contemporary MHT study showed a 9% increased cancer risk, with a decreased risk of all gastrointestinal cancer. The cancer risk was more limited than expected, with variations for MHT types, formulations and regimens.